The UK foot and ankle COVID-19 national (FAlCoN) audit – Regional variations in COVID-19 infection and national foot and ankle surgical activity. Issue 2 (February 2022) - Mason, Lyndon W; Malhotra, Karan; Houchen-Wollof, Linzy; Mangwani, Jitendra; ,; Harb, Ziad; Richardson, Ruth; Gadd, Richard; Kerr, Alexander; Clay, William; Mallick, Arijit; Bhargava, Amit; et al.
Highlights: COVID-19 has significantly impacted on the foot and ankle trauma activity in the UK. The overall COVID-19 infection rate across 6644 patients was 0.53% (35 patients). The cumulative percentage of COVID-19 infection across the audit was 1.37%. Both the COVID-19 infection rate and timing of the peaks of COVID-19 infection differed significantly across the country. National surgical activity significantly reduced for all cases during lockdown, however in the post-lockdown period there was normalisation of activity in trauma and diabetic surgery. Abstract: Aims: This paper details the impact of COVID-19 on foot and ankle activity in the UK. It describes regional variations and COVID-19 infection rate in patients undergoing foot and ankle surgery before, during and after the first national lock-down. Patients & methods: This was a multicentre, retrospective, UK-based, national audit on foot and ankle patients who underwent surgery between 13th January and 31st July 2020. Data was examined pre- UK national lockdown, during lockdown (23rd March to 11th May 2020) and post-lockdown. All adult patients undergoing foot and ankle surgery in an operating theatre during the study period included from 43 participating centres in England, Scotland, Wales and Northern Ireland. Regional, demographic and COVID-19 related data were captured. Results: 6644 patients were included. In total 0.53% of operated patients contracted COVID-19 (n = 35). The rate of COVID-19 infection was highest during lockdown (2.11%, n = 16) and lowest after lockdown (0.16%, n = 3). Overall mean activity during lockdown was 24.44% of pre-lockdown activity with decreases in trauma, diabetic and elective foot and ankle surgery; the change in elective surgery was most marked with only 1.73% activity during lock down and 10.72% activity post lockdown as compared to pre-lockdown. There was marked regional variation in numbers of cases performed, but the proportion of decrease in cases during and after lockdown was comparable between all regions. There was also a significant difference between rates of COVID-19 and timing of peak, cumulative COVID-19 infections between regions with the highest rate noted in South East England (3.21%). The overall national peak infection rate was 1.37%, occurring during the final week of lockdown. General anaesthetic remained the most common method of anaesthesia for foot and ankle surgery, although a significant increase in regional anaesthesia was witnessed in the lock-down and post-lockdown periods. Conclusions: National surgical activity reduced significantly for all cases across the country during lockdown with only a slow subsequent increase in elective activity. The COVID-19 infection rate and peaks differed significantly across the country.